Sleep quality and its relationship to mental health, physical health and health behaviours among young adults with serious mental illness enrolled in a lifestyle intervention trial. Issue 1 (16th February 2021) - Aschbrenner, Kelly A.; Naslund, John A.; Salwen‐Deremer, Jessica K.; Browne, Julia; Bartels, Stephen J.; Wolfe, Rosemarie S.; Xie, Haiyi; Mueser, Kim T.
Abstract: Aim: To characterize subjective sleep quality and examine its associations with mental health, physical health and health behaviours in a transdiagnostic sample of young adults with serious mental illness (SMI) enrolled in a lifestyle intervention trial. Methods: Baseline data from a lifestyle intervention trial with young adults (ages 18–35 years) with SMI included the Pittsburgh Sleep Quality Index (PSQI), mental health, physical health and health behaviour outcomes. Descriptive statistics and multiple linear regression were used in analyses. Results: Of 150 participants, 76% were categorized with poor sleep quality. Depressive symptoms were significantly associated with sleep quality ( β  = .438, p  < .001); however, no association was found with physical health and health behaviours. Conclusions: Young adults with SMI enrolled in lifestyle interventions may benefit from treatment that addresses sleep as part of a comprehensive approach to health promotion with attention to the role of depressive symptoms in sleep quality.